Jayne Fleener後現代課程理論的啟示 On Jayne Fleener's Postmodern Curriculum Theory and its Implication - 鍾鴻銘 Horng-Ming Jong; 單文經 Wen-Jing Shan (Higher Education Foundation, 2006)
本文旨在透過Fleener後現代課程理論的探究，以省思其對課程研究與改革可能的啟示。Fleener認為，現代主義數學化實體觀背後潛藏著一種支配性的邏輯，她主張以後現代的關係、系統、意義三種邏輯觀取而代之。奠基於此三種邏輯觀之上，Fleener認為課程應是一種機體中心的課程，此種課程強調關係、合作、整全的面向，課程因而不再是一種物件，而是機體／環境的複合體。此外，受學習型組織理念的影響，Fleener主張將學校、課程轉化為學習型組織，以強化其創造力及適應社會變遷的能力。本文最後則是根據Fleener的後現代課程理論，省思其對吾人的啟示。 The paper aims at analyzing the postmodern curriculum theory based on her recent writings on the related topics. Fleener points out that the dominant of mathematic reality of modernism should be replaced by relation, system, and meaning of postmodernism. She considers curriculum as a compound of organism-environment that emphasizes connectedness, cooperation, and well-round development, but not as single objects. She also proposes that schools should be transformed into learning organizations to strengthen their capacity of creativity and adaptation. It is hoped that the implications of her theory would give some hints to the future development of curriculum research and curriculum reform.